2007
DOI: 10.1002/aic.11133
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of a rigorous absorber model for CO2 postcombustion capture

Abstract: in Wiley InterScience (www.interscience.wiley.com).A rigorous rate-based model for acid gas absorption was developed and validated against mass-transfer data obtained from a 3-month campaign in a laboratory pilot-plant absorber in which the experimental gas-liquid material balance was within an average of 6%. The mass-transfer model is based on the penetration theory where the liquid film is discretized using an adaptive grid. The model was validated against all data and the deviation between simulated and ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
172
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(188 citation statements)
references
References 36 publications
13
172
2
1
Order By: Relevance
“…As seen from the table for MEA, the rate of stripped and absorbed CO 2 was 5.0 kg/h giving a heat demand of 4.49 kJ/kg. This is in very good agreement with previous MEA campaigns performed in the same pilot (Tobiesen et al, 2008). In Figure 3, the temperature profiles in the stripper and absorber are presented for the conditions presented in Table 3.…”
Section: Pilot Operation During 30 Wt% Mea and 50 Wt% Dea Campaignssupporting
confidence: 78%
“…As seen from the table for MEA, the rate of stripped and absorbed CO 2 was 5.0 kg/h giving a heat demand of 4.49 kJ/kg. This is in very good agreement with previous MEA campaigns performed in the same pilot (Tobiesen et al, 2008). In Figure 3, the temperature profiles in the stripper and absorber are presented for the conditions presented in Table 3.…”
Section: Pilot Operation During 30 Wt% Mea and 50 Wt% Dea Campaignssupporting
confidence: 78%
“…This latter result enables us to conclude that the column operates in the pseudo-first-order regime in which the enhancement factor is equal to the Hatta number and the mass transfer rate is independent of the liquid-side mass transfer (Danckwerts, 1970). As discussed in Raynal et al (2011), similar sensitivity toward the effective area could already be deduced from the work of Tobiesen et al (2007), even if it was not within the scope of their study. Prediction of mass transfer characteristics or packing efficiency is thus entirely given by the effective area, which calls for precise experimental or numerical determination of this parameter.…”
Section: Mass Transfer Parameters Sensitivity Analysissupporting
confidence: 58%
“…It has been shown that, when comparing simulations with the results of the Castor pilot plant, detailed simulators such as AspenTech Aspen Plus 2006.5 software with Aspen RateSep can accurately simulate the absorber performances provided that appropriate thermodynamics and kinetics corresponding to the 30wt% MEA solvent are used (Dugas et al, 2009;Tobiesen et al, 2007). RateSep is a detailed model that takes into account heat and mass transfer transport equations in both gas and liquid phases, equipment hydrodynamics and chemical reaction mechanisms to predict column performance.…”
Section: Simulations For Absorber Designmentioning
confidence: 99%
“…Another model aspect with room for different levels of detail is the thermodynamic model of the liquid phase, describing the non-ideality of the electrolyte solution. Tobiesen compares in [3] a more rigorous with simpler approaches and concludes that high accuracy is rather a matter of a good data fit than model complexity.…”
Section: Modeling Of Carbon Dioxide Removal With Chemical Absorptionmentioning
confidence: 99%